DNA barcode of seven species coral from Sepulu, Madura Island, Indonesia - INSAFITRI INSAFITRI; NINING NURSALIM; NENIK KHOLILAH; EKA MAYA KURNIASIH; NI KADEK DITA CAHYANI; WAHYU ANDY NUGRAHA; AMBARIYANTO AMBARIYANTO (Society for Indonesian Biodiversity, 2023)
Abstract. Insafitri, Nursalim N, Kholilah N, Kurniasih EM, Cahyani NKD, Nugraha WA, Ambariyanto A. 2023. DNA barcode of seven species coral from Sepulu, Madura Island, Indonesia. Biodiversitas 24: 317-323. Diversity of coral species is needed because it affects the disruption of coral reef ecosystems, nutrient recycling, coral reef growth and the habitat of biota that live in these ecosystems. The main constituents of coral reef ecosystems are coral animals that belong to the Anthozoa class. Sepulu waters (Madura Island), Bangkalan District, East Java Province, Indonesia, has a percentage of coral cover that is in the bad category, management of coral reefs in this area has not been the main focus and it is feared that the situation will get worse so efforts are needed to maintain coral reefs to be sustainable and better. This management effort requires an analysis of species identification. DNA barcoding of corals has never been done on corals of Sepulu waters. The purpose of this study is to find out the DNA of barcoding coral species on Sepulu waters. Genetic marker Cytochrome Oxidase I of the mitochondrial genome DNA (mtDNA) was used to analyze genetic diversity. Reconstruction of phylogenetic tree and genetic diversity were done by using software MEGA X. Research results showed that sample DBP011101 closely related to Dipsatraea maxima 99.55%, DBP011102 closely related to Porites rus 99.4%, DBP011103 closely related to Acropora hyacinthus 99.11%, DBP011104 closely related to Porites cf lichen 98.66%, DBP011106 closely related to Dipsastraea rotumana 95.37%, DBP011107 closely related to Porites horrisoni 98.81%, and DBP011108 closely related to Acropora valida 98.38%. The results of the study are the first coral barcode DNA on Sepulu waters that can help in determining coral species that are useful in managing the sustainability of coral resources, especially on Sepulu waters.